An integrated study resource for veterinary students at the University of Edinburgh: the library and the “Study Landscape” (Journal of EAHIL, 2016)
In 2011 the Royal (Dick) School of Veterinary Studies moved its teaching and learning activities to one campus. TheÂ Lady Smith of Kelvin Veterinary Library now links to the Study Landscape, a student-centred space for self-directedÂ learning. This allows students access to a range of physical and electronic resources including specimens and themedÂ resources. This paper presents the practical experiences of the author in collaborating with academic and technicalÂ colleagues to populate the Study Landscape with appropriate resources. This collaboration has increased ourÂ understanding of the different learning resources used in veterinary medicine and can assist us in our provision of moreÂ ‘traditional’ library services to the Veterinary School.